User-Centric Design for Automated Metering Power Management Systems: A Case Study in Nigeria - Ukeh, Orodje Edemirukaye; Edoghogho Olaye, Edoghogho x (International Journal of Applied Methods in Electronics and Computers, 2025)
Nigeria continues to face persistent power management challenges, with frequent outages affecting both urban and rural areas. Technical issues, such as open-circuit faults, contribute to significant losses in the low-voltage section of the power distribution system. Additionally, the lack of transparency in the current power management system fosters distrust between electricity consumers and providers. This study presents the Automated Metering Power Management System (AMPMS)—an integrated solution designed to improve energy monitoring, fault detection, and consumption planning. The system incorporates an automated digital meter, a Home Energy Planner (HEP), a web-based platform, and the "Meter Utility" mobile app to enhance energy management. The AMPMS utilizes a Hall effect current sensor, voltage sensor, Wi-Fi module, and Atmega328p microcontroller, enabling real-time fault detection, outage reporting, and load scheduling. Evaluation results demonstrate the system’s effectiveness in reducing power consumption. Households using the AMPMS recorded an energy consumption of 3.02 kWh, significantly lower than the 4.442 kWh observed with conventional prepaid meters—a 31.9% reduction. Furthermore, survey data revealed that 96.3% of respondents experienced delays in resolving open-circuit faults under the existing system, underscoring the need for an automated fault detection and reporting mechanism. By integrating these components, the proposed AMPMS improves power distribution accuracy, enhances consumer control over energy usage, and reduces downtime. The system is scalable for residential, small office, and potential industrial applications in developing nations. This research provides a practical and technologically driven approach to addressing Nigeria’s energy management challenges, promoting efficiency, transparency, and accountability in power distribution. Nigeria continues to face persistent power management challenges, with frequent outages affecting both urban and rural areas. Technical issues, such as open-circuit faults, contribute to significant losses in the low-voltage section of the power distribution system. Additionally, the lack of transparency in the current power management system fosters distrust between electricity consumers and providers. This study presents the Automated Metering Power Management System (AMPMS)—an integrated solution designed to improve energy monitoring, fault detection, and consumption planning. The system incorporates an automated digital meter, a Home Energy Planner (HEP), a web-based platform, and the "Meter Utility" mobile app to enhance energy management. The AMPMS utilizes a Hall effect current sensor, voltage sensor, Wi-Fi module, and Atmega328p microcontroller, enabling real-time fault detection, outage reporting, and load scheduling. Evaluation results demonstrate the system’s effectiveness in reducing power consumption. Households using the AMPMS recorded an energy consumption of 3.02 kWh, significantly lower than the 4.442 kWh observed with conventional prepaid meters—a 31.9% reduction. Furthermore, survey data revealed that 96.3% of respondents experienced delays in resolving open-circuit faults under the existing system, underscoring the need for an automated fault detection and reporting mechanism. By integrating these components, the proposed AMPMS improves power distribution accuracy, enhances consumer control over energy usage, and reduces downtime. The system is scalable for residential, small office, and potential industrial applications in developing nations. This research provides a practical and technologically driven approach to addressing Nigeria’s energy management challenges, promoting efficiency, transparency, and accountability in power distribution.